Indonesian Society is Not Disabled Friendly? - Napsiah Napsiah; Yani Tri Wijayanti (Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
The case of a state official required a Deaf person to answer questions submitted to a Deaf person on World Disabilities Day in 2021 by using spoken language and refusing to use sign language because it was considered that the disabled have the same abilities as the non- disabled group. The perception of these state officials is a representation of the Indonesian population in understanding disabilities. The purpose of this research is to prove that Indonesia already has a policy to align the life positions of disabled people with non-disabled people, but these policies do not reach the community level, so that people are not friendly to people with disabilities. This research uses descriptive qualitative method by analyzing interview data and indirect observation, as well as combining secondary data obtained from previous research, the website found that facilities in the form of infrastructure were uneven and low sign language skills for non-disabled groups led to a lack of knowledge about the existence of disabilities. The result of this study shows that the disabled group cannot adapt to their own environment so that the existence of disabilities is not widely known by the public. The lack of knowledge about people with disabilities causes people to think that disabled groups are the same as non-disabled groups. Such perception is then considered by the people of Indonesia to be unfriendly to persons with disabilities.